ROBOTICS AND MECHATRONICS FOR AGRICULTURE. - Zhang, Dan, 1964-; Wei, Bin, 1987- ([Place of publication not identified] : CRC PRESS, 2021)
The aim of the book is to introduce the state-of-the-art technologies in the field of robotics, mechatronics and automation in agriculture in order to summarize and review the improvements in the methodologies in agricultural robotics. Advances made in the past decades are described, including robotics for agriculture, mechatronics for agriculture, kinematics, dynamics and control analysis of agricultural robotics, and a wide range of topics in the field of robotics, mechatronics and automation for agricultural applications.
OCLC-licensed vendor bibliographic record.
Keywords: Robotics; Mechatronics; Agricultural innovations; SCIENCE / Life Sciences / Botany; SCIENCE / Life Sciences / General; TECHNOLOGY / Agriculture / General